Literature Study on the use of Danny Brassel’s Riddle Game for Students English Vocabulary Mastery - Yoga Muhamad Ridwan; Syamsul Rizal; Feny Martina (Jadila: Journal of Development and Innovation in Language and Literature Education, 2024)
Learning method innovation will influence learning media used and it is hoped to enhance learning qualities. There is a weakness in learning method that used as learning media. This thesis is the result of literature review, entitled “Literature Review on the Use of Danny Bressell’s Riddle Game for Students’ English Vocabulary Mastery”. The purpose of this thesis is to answer the question of the research : what is the weakness of riddle game for students’ English vocabulary mastery. This research method is library reasearch, and for the data collection through literature review from journals and article. After datas collected, then the datas analyzed through qualitative data analysis, which is the researcher uses some steps to analyze such as involving collecting the data, reducing data, presenting the data and drawing conclusion. The result is riddle game has an strongly effects for students’ english vocabulary mastery. From the data that have been analyzed, the reseacher found out a weakness from the journals and article about riddle game for students’ english vocabulary mastery, that is the researchers did not use the vocabulary test based on the curriculum at the school that they have been researched. So, to reform that weakness, there was a researcher that has a good method on the vocabulary test. She used vocabulary tests based on the curriculum where the research conducted. Based on the reasearch findings, the researcher would like to purpose some suggestions to improve teaching learning process especially teaching students’ English vocabulary by using riddle game.